The Effect of Soil Reinforcement on the Stress and Strain Field Around Underground Square-Shaped Areas and its Internal Lining Efforts in Urban Areas - Alireza Darvishpour; Asadollah Ranjbar; Amirmohammad Amiri (Civil Engineering Journal, 2018)
The passage of underground structures from the bottom of the structures on the ground causes a change in the stresses and strains created in the structure as well as the soil environment surrounding the tunnel due to the existence of an interaction between these two sides. In this way, the existence of the surface structure leads to a change in the strain and stress conditions around the tunnel, and in contrast, the tunnel also leads to a change in the stress and settlement around the structures. Therefore, such a reciprocal behavior is very important. In this research, with the help of Abaqus finite element software, two main possible conditions are considered: the creation of an underground structure in the presence of the superstructure, as well as the reverse state of the concept of constructing a building in the state in which the underground structure already exists. One of the subjects studied in this research is the physical modelling effect of the structure, rather than the effect of its wide load on the ground. Other parameters considered in this research are the number of story, the depth of the tunnel, the width of the tunnel, the thickness of the lining, the effect of changes in the soil parameters in the depth and the horizontal distance of the tunnel center from the building center. The results of this research are validated based on the results obtained by other researchers. According to the results obtained in this research, by the increase of the distance between the tunnel center and structure center and depending on the stiffness of the tunnel lining, significant asymmetric stresses are created in the superstructure. The construction of the structure before and after the tunnel construction can affect the unsymmetrical settlement of the structure The stress and strain created in the lining of the tunnel and the surrounding area are also different due to the amount of mobilized force in the reinforcements.